Kortikale und subkortikale Sprachareale im Lichte der neurokognitiven Sprachverarbeitungsmodelle - Legutko-Marszałek, Iwona (Glottodidactica, 2013)
In this article it has been pointed out that these are not only cortical but also subcortical parts of brain which participate in language processing. Apart from that, typical languageareas take part in different non-language cognitive processes. Hence the linguistic ability should not be understood as a single and separate cognitive skill which can be attributed to some particular language organ, whose function consists only in producing and analyzing linguistic signals.Language should rather be perceived as a complex phenomenon and language processing as the one consisting of many subprocesses which is indicated by neuro-cognitive models.